Pengaruh Media Pembelajaran Audio Berbasis Podcash pada Aplikasi Spotify untuk Meningkatkan Hasil Pembelajaran Maharoh Istima’ Siswa Kelas 8 SMP Muhammadiyah 06 Dau - Desi Hariyanti Harahap; Munirul Abidin (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
This study aims to develop and evaluate the effectiveness of podcast-based learning media through the Spotify application in improving listening skills (Maharah al-Istima’) of 8th-grade students at SMP Muhammadiyah 06 Dau. A quantitative research method with a quasi-experimental approach was employed, involving two groups: the experimental class using podcast media and the control class using conventional methods. Data were collected through observation and tests (pretest and posttest), and analyzed using normality, homogeneity, and independent sample t-test with SPSS 26. The results revealed that the use of podcasts significantly enhanced students’ listening skills. Students in the experimental class demonstrated higher enthusiasm, independence, and active participation compared to those in the control class. Thus, Spotify podcasts can be considered an effective and engaging alternative learning medium for Arabic language education. The study also recommends further research on a broader scale to examine long-term impacts and other influencing variables.